Treatment Decision-Making in Early-Stage Papillary Thyroid Cancer - D’Agostino, Thomas A. (Psychooncology, 2017)
OBJECTIVE: The purpose of this study was to develop an in-depth understanding of papillary microcarcinoma (PMC) patients’ decision-making process when offered options of surgery and active surveillance. METHODS: 15 PMC patients and six caregivers participated in either a focus group or individual interview. Focus groups were segmented by patients’ treatment choice. Primary themes were identified in transcripts using thematic text analysis. RESULTS: Four themes emerged from the surgery subsample: (1) Decision to undergo thyroidectomy quickly and with a sense of urgency; (2) Perception of PMC as a potentially life-threatening disease; (3) Fear of disease progression and unremitting uncertainty with active surveillance; and (4) Surgery as a means of control and potential cure. Three themes emerged from the active surveillance subsample: (1) View of PMC as a common, indolent, and low-risk disease; (2) Concerns about adjusting to life without a thyroid and becoming reliant on hormone replacement medication; and (3) Openness to reconsidering surgery over the long run. Two themes were identified that were shared by participants from both subsamples: (1) Deep level of trust and confidence in physician and cancer center; and (2) Use of physician and internet as primary sources of disease and treatment-related information. CONCLUSIONS: Several factors influenced participants’ treatment choice, with similarities and differences noted between surgery and active surveillance subsamples. Many of the emergent themes are consistent with research on decision-making among localized prostate cancer patients. Findings suggest that participants from both PMC treatment subsamples are motivated to reduce illness and treatment-related uncertainty.